2010
DOI: 10.1007/s10811-010-9543-5
|View full text |Cite
|
Sign up to set email alerts
|

Kappaphycus alvarezii (Rhodophyta, Areschougiaceae) cultivated in subtropical waters in Southern Brazil

Abstract: Four strains of Kappaphycus alvarezii were cultivated in the subtropical waters of Florianópolis, Santa Catarina State, Brazil (27°29′19′′ S/48°32′28′′ W), from February 2009 to February 2010. Seaweeds were cultivatedon floating raft near of mussel farms. Salinity ranged from 29 to 36 psu and temperature from 17.1 to 28.5°C. Higher growth rates (5.12-4.29% day −1 ) were measured in summer and autumn, showing a positive correlation between growth rate and water temperature. Lower growth rates (0.54-0.32% day −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 18 publications
1
21
2
Order By: Relevance
“…Carrageenans are extracted from red algae (Rodophyta), mainly from Kappaphycus alvarezii (Doty) Doty ex Silva, grown in Philippines. The K. alvarezii was recently introduced in Brazil for rational cultivation (Hayashi et al, 2011). Before its introduction, there were attempts to Hypnea musciformis (Wulfen) Lamouroux cultivation, a naturally found species in the Brazilian coast, with little success (Hayashi et al, 2007).…”
Section: Carrageenansmentioning
confidence: 99%
“…Carrageenans are extracted from red algae (Rodophyta), mainly from Kappaphycus alvarezii (Doty) Doty ex Silva, grown in Philippines. The K. alvarezii was recently introduced in Brazil for rational cultivation (Hayashi et al, 2011). Before its introduction, there were attempts to Hypnea musciformis (Wulfen) Lamouroux cultivation, a naturally found species in the Brazilian coast, with little success (Hayashi et al, 2007).…”
Section: Carrageenansmentioning
confidence: 99%
“…Viscosity of carrageenan crude extract solutions (1.5% w/w) was measured using a Brookfield RVDV-III rheometer (Brookfield Engineering Laboratories, model DVIII Ultra, (HAYASHI et al, 2011). Hayashi et al (2011) showed that the cultivation of K. alvarezii can be technically feasible in subtropical water and can be associated with local mussel farms, mitigating eutrophication and, eventually, increasing the profitability of farmers.…”
Section: Carrageenan Extract Analysismentioning
confidence: 99%
“…Hayashi et al (2011) showed that the cultivation of K. alvarezii can be technically feasible in subtropical water and can be associated with local mussel farms, mitigating eutrophication and, eventually, increasing the profitability of farmers.…”
Section: Carrageenan Extract Analysismentioning
confidence: 99%
“…In 2008, Hayashi et al (2011) analyzed the feasibility and the environmental risk of cultivating K. alvarezii in Santa Catarina state on the southern Brazilian coast. They concluded that the invasive risk is low and that, in the winter, the low water temperature is lethal to the species.…”
Section: Cultivation Of Kappaphycus Alvareziimentioning
confidence: 99%